Recurrent pregnancy loss at gynecology and obstetrical hospital in Duhok Province - Abdulrahman, Iman Jaafar; Jawad, Ariana Khalis; SH. M. Amin, Nasreen Abdulghafor (International Journal of Research in Medical Sciences, 2020)
Background: Recurrent pregnancy loss is physically and emotionally harmful for mothers. This study aimed to find out the prevalence and associated factors of recurrent pregnancy loss (RPL) in pregnant women in Duhok province. Methods: In this retrospective study, the medical records of the patients who had pregnancy loss and registered in Duhok Maternity Hospital were reviewed for the period of January - December 2019. Accordingly, 300 women aged 18 years and older with pregnancy loss were included in this study. Results: The prevalence of EPL was 16.3%. The study found that patients with RPL were statistically older compared to those patients without RPL, (39.27 vs. 33.24 years; P<0.001), respectively. Besides, the RPL group had a significantly higher percentage of family history of pregnancy loss (12.24% vs. 1.20%; P<0.001). The patients with RPL had significantly higher prevalence of Chlamydia trachomatis (14.29% vs. 3.59%; P=0.002), cervical incompetence (8.16% vs. 0.80%; P=0.002), structural abnormalities of uterus (14.29% vs. 4.8%; P=0.012), and polycystic ovary syndrome (PCOS) (40.82% vs. 11.95%; P<0.001). There was no significant association of RPL with smoking (P=0.261). Conclusions: This study revealed a high prevalence of RPL in patients with pregnancy loss. Also, the study showed that the patients in the RPL group were significantly older and had a higher prevalence of medical illnesses; including chlamydia trachomatis, cervical incompetence, structural anomalies of the uterus, and polycystic ovarian syndrome.